Enrichment of type I interferon signaling in colonic group 2 innate lymphoid cells in experimental colitis - Irie, Emi; Ishihara, Rino; Mizushima, Ichiro; Hatai, Shunya; Hagihara, Yuya; Takada, Yoshiaki; Tsunoda, Junya; Iwata, Kentaro; Matsubara, Yuta; Yoshimatsu, Yusuke; Kiyohara, Hiroki; Taniki, Nobuhito; et al. (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) serve as frontline defenses against parasites. However, excluding helminth infections, it is poorly understood how ILC2s function in intestinal inflammation, including inflammatory bowel disease. Here, we analyzed the global gene expression of ILC2s in healthy and colitic conditions and revealed that type I interferon (T1IFN)-stimulated genes were up-regulated in ILC2s in dextran sodium sulfate (DSS)-induced colitis. The enhancement of T1IFN signaling in ILC2s in DSS-induced colitis was correlated with the downregulation of cytokine production by ILC2s, such as interleukin-5. Blocking T1IFN signaling during colitis resulted in exaggeration of colitis in both wild-type and Rag2-deficient mice. The exacerbation of colitis induced by neutralization of T1IFN signaling was accompanied by reduction of amphiregulin (AREG) in ILC2s and was partially rescued by exogenous AREG treatment. Collectively, these findings show the potential roles of T1IFN in ILC2s that contribute to colitis manifestation.